2021
DOI: 10.3389/fcell.2021.723057
|View full text |Cite
|
Sign up to set email alerts
|

Characterized the Adipogenic Capacity of Adipose-Derived Stem Cell, Extracellular Matrix, and Microenvironment With Fat Components Grafting

Abstract: Background: Autologous fat grafting has been a widely used technique; however, the role of adipose-derived stem cells (ASCs), extracellular matrix (ECM), and microenvironment in fat regeneration are not fully understood.Methods: Lipoaspirates were obtained and processed by inter-syringe shifting to remove adipocytes, yielding an adipocyte-free fat (Aff). Aff was then exposed to lethal dose of radiation to obtain decellularized fat (Df). To further remove microenvironment, Df was rinsed with phosphate-buffered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Besides, many researchers tend to use cross-linking to block the binding sites of the d-ECM, 112 delaying the exposure of active structural domains. It also reduces the involvement of d-ECM components in regulating inflammatory responses by loading cells 113,114 to prolong the degradation of the d-ECM to achieve the best tissue remodeling effect. However, specific residual components are necessary for structural support and functional involvement in mediating immune cell responses.…”
Section: Reviewmentioning
confidence: 99%
“…Besides, many researchers tend to use cross-linking to block the binding sites of the d-ECM, 112 delaying the exposure of active structural domains. It also reduces the involvement of d-ECM components in regulating inflammatory responses by loading cells 113,114 to prolong the degradation of the d-ECM to achieve the best tissue remodeling effect. However, specific residual components are necessary for structural support and functional involvement in mediating immune cell responses.…”
Section: Reviewmentioning
confidence: 99%
“…In the process of exploring the mechanism of this part of the experiment, we detected the expression of classical angiogenesis and adipogenesis factors (PPARγ, bFGF, VEGF, C/EBPα, C/EBPβ, FABP4, Leptin, Adiponectin, IGF1, GAPDH [ [16] , [47] , [49] ]). We found that only VEGF, C/EBPα and IGF1 were significantly increased in the co-culture group of ADSCs and fibroblasts compared to ADSCs cultured alone ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantage of SVF is that its cell population is complex and the proportion of its cell population cannot be standardized during the SVF isolation process, making the final fat retention rate still very uncertain [ 8 , 15 ]. In addition, it is worth mentioning that one study showed that fat grafting utilizing SVF rather than ADSCs as its CAL component had higher long-term retention rates, suggesting that other cells in SVF may contribute to fat retention rates improvement [ 16 ]. Based on this, we focused our research on fibroblasts that produce ECMs.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous study just showed that adipose ECM and microenvironment possess the capability to promote early adipogenesis, while the ECM alone cannot induce adipogenesis in vivo . ADSCs can adjust early adipogenesis with angiogenesis and tissue remodeling by directly differentiating into endothelial cells and regulating macrophage polarization, contributing to better long-term retention and greater tissue integrity ( 55 ). Few studies have explored the relationship between CCNB1 and adipogenic differentiation in human ADSCs, and this association is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%